Manajemen Edukasi Terhadap Pencegahan Low Back Pain (LBP) pada Ikatan Keluarga Madrasah Raudatul Ulum Surakarta - Yulia Dewi; Redita Salma Ayusandra Pramesti; Dinda Armita; Wahyu Tri Sudaryanto (Jurnal Pengabdian Masyarakat, 2022)
Low Back Pain (LBP) is pain that is felt in the lower back area, it can be local pain or radicular pain or both. This pain is felt between the angles of the lower ribs and the folds of the lower buttocks, namely in the lumbar or lumbosacral area and is often accompanied by radiating pain to the legs and feet. The incidence of low back can be associated with several risk factors such as occupational characteristics, environmental factors, physical activity, and genetic factors, high body mass index, lifestyle, and smoking habits. From the results of observations, it was obtained primarily that the community had health problems in the form of lower back caused by post-activities at the cottage and active post-lectures due to the COVID-19 pandemic. Rebana or Hadroh training, training on modern musical instruments, some of which can trigger LBP.